Tractatus logico-philosophicus - "Wittgenstein, Ludwig" (London, 2008)
This is the fundamental texts of twentieth century philosophy-short-, bold, cryptic, and remarkable in its power to stir the imagination of philosophers and non-Michael Frayn
Keywords: "Logic, Symbolic and mathematical"